Virology : molecular biology and pathogenesis - Norkin, Leonard C. (Washington, DC : ASM Press, 2010)
"Based on the author's experiences teaching virology for more than 3 5 years, Virology: Molecular Biology and Pathogenesis enables readers t o develop a deep understanding of fundamental virology by emphasizing p rinciples and discussing viruses in the context of virus families. More over, individual virus families are examined within the context of the Baltimore classification system, a key unifying theme that allows reade rs to assume basic facts about the replication strategy of a virus base d on the nature of its genome."--BOOK JACKET.
A selective history on the nature of viruses -- Biosynthesis of viru ses : an introduction to virus classification -- Modes of virus infecti on and disease -- Host defenses and viral countermeasures -- Reoviruses -- Picornaviruses -- Flaviviruses -- Togaviruses -- Coronaviruses -- R habdoviruses -- Paramyxoviruses -- Orthomyxoviruses -- Miscellaneous RN A viruses -- Parvoviruses -- Polyomaviruses -- Papillomaviruses -- Aden oviruses -- Herpesviruses -- Poxviruses -- The retroviruses : the RNA t umor viruses -- The retroviruses : lentiviruses, human immunodeficiency virus, and AIDS -- Hepadnaviruses and hepatitis delta virus.
Includes bibliographical references and index.
Keywords: Virology -- Textbooks; Molecular virology -- Textbooks; Virus diseases -- Pathogenesis -- Textbooks; Viruses -- pathogenicity; Genome, Viral; Virus Diseases -- Etiology; Viruses -- genetics